Inequality and Emancipation : An Educational Approach - Gross, Stefan (Journal of Education and Research, 2010)
Emancipation has lost its charisma. In the 1960s, the term had been one of the saviour-concepts in the educational debate on social inequality and the political function of pedagogy in Western countries. Nowadays, as the discussion is still ongoing, the word is rarely in use. Overloaded with political enmeshments and a plurality of meanings, emancipation seems to be nothing more than a nearly forgotten relict of an ancient time. How could this rise and fall happen? The present essay is tracing the colourful history of emancipation in various contexts, recapitulating its pedagogical importance in the 1960s and discovering how the pillars have kept their primary function, although the word is not in use any longer. DOI: http://dx.doi.org/10.3126/jer.v2i0.7617 Journal of Education and Research Vol. 2, 2010 p.9-16